Progress and Prospect of Liquid Crystal Droplets - Le Zhou; Tingjun Zhong; Huihui Wang; Ke Xu; Pouya Nosratkhah; Kristiaan Neyts (Crystals)
Liquid crystal (LC) droplets are highly attractive for applications in privacy windows, optical switches, optical vortices, optical microresonators, microlenses, and biosensors due to their ease of fabrication and easy alignment at surfaces. This review presents the latest advancements in LC droplets, which have nematic, chiral nematic, and twist–bend nematic and ferroelectric nematic phases, or blue phases. Finally, it discusses the challenges and opportunities for applications based on LC droplets. The main challenges encompass the precise control of internal structures and defects to meet diverse application requirements, enhancing stability and durability across various environments, reducing large-scale production costs to improve commercial feasibility, increasing response speeds to external stimuli to adapt to rapidly changing scenarios, and developing tunable LC droplets to achieve broader functionalities.